KEANEKARAGAMAN AMFIBI DAN REPTIL DI KAWASAN WISATA SITU BAGENDIT DAN SEKITARNYA, KABUPATEN GARUT PROVINSI JAWA BARAT - Kurnia, Insan; Nurfadhilah, Nyimas Aisyah; Syahrahmani, Aluna; Liani, Hikmah Rachma; Lawana, Dewa Dzullfadhil; Nathaniel, Bernado Raphael (Fakultas Kehutanan Universitas Winaya Mukti, 2024)
Amphibians and reptiles are two groups of wildlife that are ecologically close and related to aquatic ecosystems. Setu Bagendit is a freshwater ecosystem with a variety of other habitats around it. The research aims to analyze diversity of amphibians and reptiles in Setu Bagendit Tourism Area and its surroundings. The research was carried out in June 2023 using a combination of a 100 meter transect method and time search of 30 minutes. Data analysis was carried out qualitatively and quantitatively by diversity index (H'), evenness index (E) and similarity index (SI). There were a total of 18 species of amphibians and reptiles from two orders and 11 families. All species are cosmopolitan, that widely distributed with high adaptability to live in disturbed habitats and close to human living environments. The values of H' obtained ranged from 0.56-2.37, while E values obtained ranged from 0.78-0.87. The SI ranges from 0.00-0.64.